RQdeltaCT: an open-source R package for relative quantification of gene expression using delta Ct methods - Daniel Zalewski; Anna Bogucka-Kocka (Scientific Reports)
Abstract Relative quantification of gene expression is a fundamental method used in the molecular biology field to analyse real-time PCR data to determine transcriptional differences between groups of samples (or technical replicates of a single sample). The main methods used for relative quantification of gene expression are delta Ct methods that allow to compare means of gene expression between groups of samples without preparing a standard curve. Despite the availability of several tools for delta Ct methods, it is difficult to select the best one that would be characterized by sufficient flexibility and comprehensive functionality. Therefore, we developed the RQdeltaCT R package, which was designed to analyse real-time PCR data for the relative quantification of gene expression using delta Ct methods (including 2−dCt and 2−ddCt methods), either to compare independent groups of samples or groups with paired samples. Furthermore, the package offers functions that cover other essential steps of analysis, including importing datasets, multistep quality control of data, numerous visualisations, and enrichment of the standard workflow with additional analyses (correlation analysis, Receiver Operating Characteristic analysis, linear and logistic regression). All obtained results can be conveniently saved as tables and publication-ready images. The RQdeltaCT package has been designed with the intention of being friendly to beginners in R programming. The package (version 1.3.2) is freely available on the GitHub ( https://github.com/Donadelnal/RQdeltaCT ) and CRAN ( https://CRAN.R-project.org/package=RQdeltaCT ) repositories.